Reduction of Urea Fertilizer Uses through Application of Livestock Manures in An Integrated Farming of Maize and Cattle - Suwarto Suwarto (Journal of Tropical Crop Science, 2018)
Crops and livestock have historically been grown together in an integrated farming; this system facilitates sharing of nutrient and land resources, and benefiting both operations. The current study examined integrated farming of maize and cattle in Waleran Village, East Java, Indonesia. In maize cultivation, the farmers apply 10 ton of the manure, 300 kg Urea (46% N) and 300 kg NPK Phoska (N:P2O5:K2O = 15%:15%:15%) per hectare. However, more nitrogen had actually been applied when manure is added, increasing the amount of nitrogen by 180 kg N.ha-1 which consequently a waste.  Therefore, more efficient application of nitrogen in maize production needs to be studied.  A field experiment was conducted from November 2017 to March 2018 using maize “Pioneer 32”. The study was organised in a completely randomized block design consists of 10 m x 10 m plots and four replications. The crops were fertilized with nitrogen at 46, 91, 137 and 183 kg.ha-1. Two seeds of maize were planted per hole with planting distance of 70 cm between rows and 40 cm within row. Plant growth were measured weekly at four to eight weeks after planting; yield variables were measured at harvest. The increasing nitrogen levels did not significantly influence the maize growth or yield.  The manure contributed about 114 kg.ha-1nitrogen supply.  The lowest total nitrogen fertilizer applied (159 kg.N ha-1) resulted in the optimum leaf area index (4.65) and leaf nutrient content of N (2.70%) and P (0.26%) which is above to the critical leaf nutrient content with maize grain yield of 6.19 ton ha-1. The manure in integrated farming could reduce the use of Urea due nitrogen contribution from the livestock manures.               Keywords:  maize growth, nitrogen levels, leaf area index, leaf nutrient content